The prevalence of overt and subclinical thyroid disorders in the adult population of Malaysia - Shahar, Mohammad Arif; Omar, Ahmad Marzuki; Ab Wahab, Norasyikin; Sukor, Norlela; Kamaruddin, Nor Azmi (Korean Thyroid Association, 2017)
To determine the prevalence of thyroid dysfunction among the Malaysian adult population A cross sectional study involving 2259 subjects selected from 5 pre-assigned regions which were representative of the socioeconomic and geographical background in Malaysia was performed. Sixty-nine subjects were excluded due to incomplete data. The prevalence of thyroid dysfunction was also determined in 2054 subjects who did not report any history of thyroid diseases nor taking any thyroid medications (disease-free population). Hundred thirty-six (136) subjects with known thyroid disorders were analysed in detail. The hormonal assays and thyroid antibodies were performed using chemiluminescent microparticle immunoassays by the Architect and Immulite systems respectively. Overt and subclinical hypothyroidism were defined as TSH > 5.00uIU/mL with free thyroxine (T4) < 9.10pmol/L and fT4 within the reference range (9.10 - 23.80pmol./L) respectively. Overt and subclinical hyperthyroidism were defined as TSH < 0.32uIU/mL with fT4 > 23.80pmol/L and fT4 within the reference range respectively. The overall prevalence of overt hypothyroidism was 0.5%; subclinical hypothyroidism 1.6%; overt hyperthyroidism 0.6% and subclinical hyperthyroidism 2.8%. The prevalence of thyroid dysfunctions in the disease-free population were: overt hypothyroidism 0.3%; subclinical hypothyroidism 1.1% and subclinical hyperthyroidism 2.0%. Among those with history of thyroid disorders, 57.1% subjects on L-thyroxine and 48.0% subjects on anti-thyroid drugs were found to be euthyroid. Hyperthyroidism was associated with detectable antiTPO and antiTG. Female had a higher preponderance for thyroid dysfunction across all ages. There was however no significant difference in the prevalence of thyroid dysfunctions between various geographical locations (urban vs rural; coastal vs inland), age and ethnicity. The prevalence of overt hypothyroidism and hyperthyroidism in the adult population of Malaysia were 0.5% and 0.6% respectively with higher preponderance in females as observed in other studies. While the prevalence of the subclinical entities of both hypo and hyperthyroidism were 1.6% and 2.8% respectively.